Efektifitas Penggunaan Komik Disiplin Belajar Dalam Layanan Bimbingan Konseling di MTss Ulumul Quran Banda Aceh - Isnia, Isnia; Nuzliah, Nuzliah (PEMA, 2025)
The low level of learning discipline among students at MTsS Ulumul Qur’an Banda Aceh is reflected in their tendency to procrastinate, arrive late, and show limited responsibility toward academic tasks. This condition affects both motivation and learning achievement. This study aims to examine the effectiveness of using educational comic media in improving students’ learning discipline through group guidance services. The research employed a quantitative approach with a quasi-experimental method using a One Group Pretest–Posttest Design. The subjects were five eighth-grade students selected purposively based on preliminary observation results. The instrument used was a Likert-scale questionnaire consisting of four indicators: compliance with learning rules, regularity in study habits, responsibility for assignments, and time management. The pretest results showed an average score of 67.80, which increased to 88.40 in the posttest. The t-test obtained a significance value of 0.000 (p < 0.05), indicating a significant difference before and after treatment. The N-Gain value of 72.15% demonstrates that the use of comic media was effective. Therefore, educational comics proved effective in improving students’ learning discipline by fostering understanding, responsibility, and learning motivation. The findings highlight the importance of using creative visual media in guidance and counseling services to strengthen students’ discipline and character development in madrasah settings.